Embracing Mobile-Based Spaced Learning to Enhance English Scientific Vocabulary Mastery and Academic Performance among ESP Students - AbdAlgane, Mohammed; Elkot, Mohamed Ali; Ali, Rabea (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Mobile-based spaced learning, an educational approach that divides learning into timespaced periods, has been widely studied in language education, particularly English. However, research on its application in English for Specific Purposes (ESP) contexts, especially within mobile-based spaced learning environments, and its differentiated effects on vocabulary mastery and academic performance remains limited. This study aimed to investigate the impact of mobile-based spaced learning (equal or expanded) on English scientific vocabulary mastery and academic performance among ESP students, specifically scientific lab majors. Sixty students were divided into two groups: those who learned in an equal-spaced style and those who learned in an expanded-spaced style. Data was collected through vocabulary and academic tests, and a quasi-experimental method was employed. The study found that both equal-spaced and expanded-spaced learning enhanced vocabulary acquisition, but only the expanded-spaced learning method significantly boosted academic performance. While both methods improve vocabulary, the extended reinforcement of expanded spaced learning may enhance cognitive activities and long-term retention. The findings suggest that expanded-spaced instruction may particularly benefit cognitively demanding subjects within ESP courses. Further research is needed to examine the long-term effects and applicability of these strategies to different courses and students and to investigate the interaction between spaced learning strategies and learner characteristics.